Czas powieściowy i jego gramatyczno-stylistyczne artykulacje (na przykładzie polskiego tłumaczenia powieści Georges Pereca) - Warchoł, Jadwiga (Stylistyka, 2021)
The subject-matter of our considerations is a reflection on form and way of construc- ting fictional space-time in the novel of the XXth Century; to whose trend should be clas- sified as well Georges Perec’s book “Vie, modę d’emploi”, translated into Polish langu- age and published in 2001.In our study, we desire to explain out only stylistic symptoms of time dimension of this novel. No accidently our central subject of considerations is qu- alified as “time dimension of the work”, because analysing the whole novel through structure of its individual chapters (particularly the chapter XXVI), we can notice, that the time is a function of space.Formally ”spatial” constructing of time dimension in this book depends on sections of time, expressed in narrative present tense, matching with surrounding sight of space of individual flats (corresponding to ąuantity of chapters - 99), at simultaneous temporal “bringing out” the biographical facts of their occupants in diffe- rent time’s profiles. Arrangement of puzzle by one of heroes, painting a their common bu- ilding’s picture by another one, or else writing a novel by narrator himself, through te- sting, seizing or “subjugating” the time can lead to annihile it. Methodical background for these analyses would be the thesis advanced by Paul Ricoeur, first of all in his work” “Le temps et le rćcit” (Ricoeur 1983: t.I) understanding the category of narration as iden- tifying discourse, from point of sight of narrator, “timed” inside of this discourse.However if we will compare quoted fragments with original text, it will tum out, that polish translation permits to recognize the principle problem of time in this book, repre- sented as a function of space; at other side, the time with its spatial symptoms as annihila- tion, death (virginal whiteness of paper leaves or black hole). But one should yet be noti- ced, that utilization of formal value of grammatical times of French linguistic system, very most important factor in fictional construction in this work, does not have exact equ- ivalents in Polish language (Dąmbska-Prokop 2005).